إعادة صياغة البحث العلمي في العقيدة الإسلامية - الأمين، أحمد عبدالصمد محمد (جامعة الزعيم الأزهري, 2014)
تناولت الدراسة تعريف العقيدة ومنزلتها وأهمية البحث فيها وضرورة إعادة صياغة البحث العلمي فيها، وعدد من الموضوعات ذات الصلة، مفصلة في خطة البحث، وتأتي أهمية الدراسة لكونها تتناول موضوعاً مهماً وهو إعادة صياغة البحث العلمي في العقيدة، ومناهج البحث في علم العقيدة، وهو علم حديث لم ينضج بعد. وتهدف الدراسة إلى عدة أهداف منها: بيان المقصود بإعادة صياغة البحث العلمي في العقيدة وتوضيح مسوغات إعادة صياغة البحث في العقيدة، والتعريف بمناهج البحث في علم العقيدة، والكشف عن الصعوبات التي تواجه الباحثين في عصرنا الحاضر. وتجيب الدراسة عن عدد من الأسئلة منها: ما هو المقصود بإعادة صياغة البحث في العقيدة الإسلامية ؟ وما هي الجوانب المهمة في إعادة الصياغة ؟، وهل هناك مسوغات لإعادة صياغة البحث في العقيدة ؟ وما هي المناهج المتبعة في البحث في العقيدة ؟. المنهج المتبع في الدراسة وهو المنهج الوصفي التحليلي. وتوصلت الدراسة إلى نتائج من أهمها: حاجة العقيدة الإسلامية إلى إعادة صياغة البحث فيها، منهج السلف من الصحابة والتابعين هو المنهج الحق في التلقي والاستدلال. وقد خلصت الدراسة إلى توصيات منها: ضرورة الاهتمام بالجوانب العلمية المختلفة في إعادة صياغة البحث العلمي في العقيدة الإسلامية عرض العقيدة الإسلامية عرضاً تقريرياً وتأسيسياً كما عرضها القرآن الكريم بعيداً عن المناهج الكلامية الفلسفية. The study definition of belief, rank, and the importance of research and the need for the reformulation of the scientific re¬search, and a number of relevant topics , in a detailed research plan. the importance of the study because it addresses an impor¬tant topic, a reformulation of scientific research in the creed, and research methods in the science of faith, which modern science has not yet matured . The study aims to several objectives, including: a state-ment intended to re formulation of scientific research in the faith, and to clarify the rationale for reformulation of research in doc¬trine, the definition and methods of research in the science of faith, and disclosure of the difficulties faced by researchers in our time. Study and answer a number of questions including: What is meant by the reformulation of research in the Islamic faith? What are the important aspects in re - drafting? , Is there a rationale for the refor¬mulation of research in doctrine? What are the approaches in the search of religious beliefs? . Approach of the study is descriptive analytical method. The study found the results of the most impor¬tant: the Islamic faith is a need to reformulate the search, approach the predecessor-of the companions and followers s the right to receive the curriculum and reasoning. The study reformulate the search, approach the predecessor of the companions and differ¬ent aspects of scientific reformulation of scientific research in the Islamic faith, the Islamic faith offer reportorial and foundational as presented by the Koran away from the philosophical approaches of words.
Keywords: التشريع الإسلامي -- الفقه الإسلامي -- العقيدة الإسلامية -- البحوث العلمية